Study on Ultraviolet Aging Performance of Composite Modified Asphalt Based on Rheological Properties and Molecular Dynamics Simulation - Mingxing Gao; Conghao Fan; Xinxin Chen; Meijian Li (Advances in Materials Science and Engineering)
In order to study the effect of UV aging on asphalt performance, the asphalt four-component test, dynamic shear rheology test, and flexural creep stiffness test were combined with molecular dynamics simulation to matrix asphalt and rubber powder/styrene-butadiene rubber/polymerization. The properties of phosphoric acid/epoxy resin modified asphalt before and after UV aging were analyzed, and the mechanism of UV aging was discussed. Research shows that modified asphalt has better high and low temperature performance and mechanical properties than matrix asphalt. After aging, the asphaltene content increases, and the gum and light components decrease. When unaged, the modified asphalt has more asphaltenes than the matrix asphalt, and the change after UV aging is less than the matrix asphalt. With the progress of UV aging, the rutting factor gradually increases, the phase angle gradually decreases, and the high-temperature performance of the asphalt is improved; the stiffness modulus gradually increases, the creep rate gradually decreases, and the low-temperature capability of the asphalt is weakened; cohesive energy density increases, the intermolecular interaction becomes stronger, and the solubility parameter becomes smaller, which reduces the compatibility between the asphalt and the modifier and increases the elastic modulus, bulk modulus, and shear modulus, improving the high-temperature mechanical properties of the asphalt. Based on the rheological properties, composition changes, and molecular model parameters of the modified asphalt, the anti-ultraviolet aging ability of the modified asphalt is better than that of the matrix asphalt.